Mechanism Design and Simulation Analysis of Deformable Wheeled Mobile Robot - Peichao Cong; Junjie Liu; Xinjie Feng (Jixie chuandong)
Aiming at the problems of the deformation wheel posture adjustment and lower step buffering of the current deformable wheel mobile robot， a novel deformable wheel mobile robot is designed based on the mechanical self-locking principle. With the self-locking effect between the "push rod" and the "plane screw pair"， the lifting universal wheel mechanism is set up， which effectively solves the "wheel plate retraction" phenomenon of the deformation wheel， and optimizes the mechanism of the system control. The robot has a lifting universal wheel mechanism， which can effectively guarantee the obstacle crossing ability of the system and reduce the impact effect in the process of descending the steps. Through the design of key structural dimensions such as wheel radius and center distance， the obstacle crossing stability of robot is improved. Finally， the effectiveness of the design scheme is verified by simulation analysis.